EXAMANING FREQUENCY OF SECONDARY SCHOOL STUDENTS’ USE OF INTERNET AND SOCIAL NETWORKS - Mustafa YAĞCI; Murat IŞIK (International Journal of Eurasia Social Sciences, 2015)
Nowadays, interest on social network sites (SNS) is growing like wildfire. SNS used for different purposes effect people’s life in a way. SNS has led to remodelling many areas like People communicate, family interaction, business profile and learning process & method. Today, millions of people communicate on social networks and they interact with each other in various ways. In this paper, we examine frequency of Internet and Social Networking on students of Secondary education. And analyse the result with some variables such as gender, age and purpose of usage. According to the research results, there are statistical differences between usages of Internet & Social Networking and gender & age although there is no significant difference between usages of Social Networking and student class.